SWOT Analysis of Halal Tourism Development in West Sumatra - Rozalinda; Nuhasnah Nuhasnah (UIN Mataram, 2021)
Since winning the World Best Halal Culinary Destination and World's Best Halal Destination award at the World Halal Tourism Award 2016, West Sumatra has increasingly shown its potential as the world's halal tourism destination. With the establishment of West Sumatra as a halal destination, there is a great opportunity for local governments to develop the sharia tourism sector in this area. The objective to be achieved in this study is to develop a halal tourism development strategy in West Sumatra. The location of the study was carried out on tourist objects that were visited by many tourists in West Sumatra. Data sources were obtained from the provincial and district / city Tourism and Creative Economy Development Office, the Central Bureau of Statistics, business actors and tourists. Data was collected through observation, questionnaires, interviews, and documentation. Data analysis techniques use SWOT analysis. The results of the study show that West Sumatra has a very potential halal tourist destination. Supported by sharia-style hotels, the availability of religious facilities, andhalal culinary. The development of halal tourism provides opportunities for improving the economy of the community. Therefore, the strategic plan that must be carried out in the development of halal tourism in West Sumatra is to establish regulations on halal tourism, socialization, guidance for business actors. Then the government provides halal certificate facilities for businesses, infrastructure improvements.